RELATIONSHIP BETWEEN MOTHER'S KNOWLEDGE ABOUT CLEAN AND HEALTHY BEHAVIOR (PHBS) AND DIARRHEA IN CHILDREN AGED 0-3 YEARS AT THE AEK NAULI HEALTH CENTER IN PEMATANGSIANTAR - Doortua; Jeni Raulina Br Siregar; Minda Rahel Simatupang (PT. Radja Intercontinental Publishing, 2021)
The incidence of diarrhea is the inadequate provision of clean water, water contaminated with feces, lack of sanitation facilities, unhygienic disposal of feces, dirty personal and environmental hygiene, and inappropriate food preparation and storage. Many factors directly or indirectly become factors driving the occurrence of diarrhea, consisting of agent, host, environment and mother's lack of knowledge about clean and healthy living behavior. The purpose of this research is aHaUh to find out the relationship between mother's knowledge about clean and healthy living behavior (PHBS) and the incidence of diarrhea in children aged 0-3 at the Aek Nauli Health Center in 2017. This type of research is descriptive quantitative with a cross-sectional research design. The population in this study were all mothers who had children aged 0-3 years who came to visit the Aek Nauli Health Center in 2017 with an average monthly visit of 30 people. Sampling using a total sampling technique of 30 people. Based on the results of the study, the majority of mothers' knowledge about PHBS at the Aek Nauli Health Center had less knowledge, as many as 22 people (73,300). The majority of respondents reported that the incidence of diarrhea at the Aek Nauli Health Center was 25 people (83 30). For this reason, it is hoped that mothers will increase their knowledge about PHBb by seeking more information, especially from health workers so that the incidence of diarrhea in children is reduced.